Анализ рынка жилой недвижимости Украины и АР Крым - Кондрашова, Г.П. (Культура народов Причерноморья, 2014)
В статье проанализированы основные тенденции развития рынка жилой недвижимости
Украины и АР Крым в 2013 году, выявлены причины депрессивного развития рынка недвижимости,
определены пути стабилизации его развития в стране.
Ощутимым резервом дальнейшего эффективного развития рынка жилой недвижимости на Украине
могут стать эффективно развивающиеся банковская и государственная жилищные ипотеки. Для этого
коммерческим банкам Украины необходимо разрабатывать и проводить более взвешенную депозитную
политику, повышать объемы получаемой чистой прибыли. Государство должно и далее своевременно
выделять дешевые государственные ресурсы на ипотечное жилищное кредитование. В статті проаналізовані основні тенденції розвитку ринку житлової нерухомості України і
АР Крим в 2013 році, виявлені причини депресивного розвитку ринку нерухомості, визначені шляхи
стабілізації його розвитку в країні.
Відчутним резервом подальшого ефективного розвитку ринку житлової нерухомості в Україні можуть
стати банківська і державна житлові іпотеки, що ефективно розвиваються. Для цього комерційним
банкам України необхідно розробляти і проводити більше зважену депозитну політику, підвищувати
обсяги отримуваного чистого прибутку. Держава повинна і далі своєчасно виділяти дешеві державні
ресурси на іпотечне житлове кредитування. In the article basic progress of dwelling property of Ukraine market trends and are analysed
Autonomous Republic of Crimea in 2013, reasons of the depressed market of the real estate development are
educed, the ways of stabilizing of his development are certain in a country and her regions.
In 2013 part of foreign investors went away from the Ukrainian property market, that affected financing of
building projects and efficiency functioning of some segments of the real estate (in particular, hotel). The care of
foreign capitals from Ukraine is explained first of all by imperfection of legislative base of Ukraine and
instability of the Ukrainian economy and politics.
An effectively developing bank and state housing mortgage can perceptible reserve of stabilizing and further
effective market of the dwelling real estate development become on Ukraine. For realization of these possibilities
the commercial jars of Ukraine must develop and conduct more self-weighted deposit politics (for the decline of
cost of credit resources), to promote the volumes of the got net income. The state must and further to develop the
government mortgage housing programs, regularly and in good time to distinguish cheap state resources on the
mortgage housing crediting. On condition of softening of requirements to the profile of borrower, increase of
amount of objects participating in the program (especially in regions), long-term securing of item of budget for
indemnification of interest rates such housing programs would become much more effective and more popular.